A review on mechanical properties and wear behaviour of aluminium based metal matrix composites. (2021) - Chelladurai, Samson Jerold Samuel; Kumar, S. Senthil; Venugopal, Narasimharaj; Ray, Abhra Pratip; Manjunath, T.C.; Gnanasekaran, S.
Abstract: Aluminium based metal matrix composites have been widely used in various applications such as automotive, defense, marine, electronics and automobile sectors because of its excellent strength to weight ratio, excellent stiffness to weight ratio with better resistance to wear and corrosion. The mechanical properties of matrix are strengthened by reinforcing particles, fibers and whiskers. These reinforcements act as load bearing elements which resists cracks during its applications. Wear is one of the predominant factors and wear resistance can be improved by increasing the hardness of material. These composites can be made by various manufacturing process such as solid state process and liquid metallurgy route. The review of mechanical properties and wear resistance of aluminium matrix composites by various manufacturing processes have been discussed.